SIRT2-mediated deacetylation and tetramerization of pyruvate kinase directs glycolysis and tumor growth - Park, Seong-Hoon (Cancer Res, 2016)
Sirtuins participate in sensing nutrient availability and directing metabolic activity to match energy needs with energy production and consumption. However, the pivotal targets for sirtuins in cancer are mainly unknown. In this study, we identify the M2 isoform of pyruvate kinase (PKM2) as a critical target of the sirtuin SIRT2 implicated in cancer. PKM2 directs the synthesis of pyruvate and acetyl-CoA, the latter of which is transported to mitochondria for use in the Krebs cycle to generate ATP. Enabled by a shotgun mass spectrometry analysis founded on tissue culture models, we identified a candidate SIRT2 deacetylation target at PKM2 lysine 305 (K305). Biochemical experiments including site-direct mutants that mimicked constitutive acetylation suggested that acetylation reduced PKM2 activity by preventing tetramerization to the active enzymatic form. Notably, ectopic overexpression of a deacetylated PKM2 mutant in Sirt2-deficient mammary tumor cells altered glucose metabolism and inhibited malignant growth. Taken together, our results argued that loss of SIRT2 function in cancer cells reprograms their glycolytic metabolism via PKM2 regulation, partially explaining the tumor-permissive phenotype of mice lacking Sirt2.